Simulasi Identifikasi Makrozoobentos Sebagai Bioindikator Kualitas Air Di Universitas Nias - Gea, James Hendrafor; Telaumbanua, Andika Taufik Perdamaian (Jurnal Perikanan dan Kelautan, 2025)
Macrobenthos are benthic organisms measuring more than 0.5 mm that live at the bottom of waters such as rivers, lakes, and seas. These organisms play a crucial role in maintaining the balance of aquatic ecosystems, both as decomposers of organic matter, as part of the food chain, and as bioindicators of aquatic environmental quality. This study aims to identify macrobenthos species through image-based visual simulations and to evaluate the potential of each species in indicating water quality conditions. The methods used include morphological classification using simple identification keys, group discussions, and analysis of species tolerance levels to pollution. Five species were identified: Perna viridis, Scylla serrata, Litopenaeus vannamei, Nereis virens, and Panulirus versicolor, which showed varying tolerance levels to water pollution from low to high. These findings reinforce the use of macrobenthos as an effective and economical biological monitoring tool, particularly in educational activities and water resource management. Visual simulations have proven to be a relevant method for enhancing students' understanding of aquatic biodiversity while raising awareness of the importance of aquatic environmental quality.